1998
DOI: 10.1191/095968398670694506
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and titanium in peat profiles as indicators of human impact

Abstract: A close correlation exists at four peat sites between pollen indicators of human impact, especially Plantago lanceolata and Cerealia, and the elements silicon and especially titanium as indicators of erosion. Pollen of plants with a short life cycle occur at the peak of silicon or titanium or shortly after, and a treepollen response follows later. Short disturbances of the vegetation or very early human impact can be detected and delimited even better by the increase of these elements than by pollen analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
2
28
0
2
Order By: Relevance
“…The elevated detrital input was also supported by high Ti and Si concentrations, which have been shown to be good indicators of soil erosion (Hölzer and Hölzer 1998). Ti rarely exists in plants, though Si can be found in plants such as Cyperaceae, Equisetum, or diatoms (Hölzer and Hölzer 1998). However, the strong correlation of Ti and Si in the DJH profile suggests that an increase in Si is likely caused by the erosion of mineral soils.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The elevated detrital input was also supported by high Ti and Si concentrations, which have been shown to be good indicators of soil erosion (Hölzer and Hölzer 1998). Ti rarely exists in plants, though Si can be found in plants such as Cyperaceae, Equisetum, or diatoms (Hölzer and Hölzer 1998). However, the strong correlation of Ti and Si in the DJH profile suggests that an increase in Si is likely caused by the erosion of mineral soils.…”
Section: Discussionmentioning
confidence: 98%
“…The high Ti and Si concentrations in DJH profile after 1300 cal BP correspond with a continuous occurrence of Cerealia pollen, suggesting landscape instability and soil erosion after forest clearance and agricultural activities (e.g. Hölzer and Hölzer 1998). The dry conditions after 700 cal BP, as indicated by the plant macrofossil results, might have been due to human activities through peat mining and altered drainage.…”
Section: History Of Human Influences Derived From the Peat-core Recordmentioning
confidence: 99%
“…Hölzer and Hölzer, 1998), it is possible to use it to calculate an atmospheric soil dust content (Shotyk et al, 1998). Because Ti is conservative, it can be assumed that its concentration in 'soil dust' is generally similar to its concentration in the upper continental crust (0.40%, McLennan, 2001) and the soils from which it is eroded.…”
Section: Human Vs Climatic Signals During the Last Millenniummentioning
confidence: 99%
“…Other studies have shown that silicon, aluminium, titanium and zirconium, together with rare earth elements (REE) are valuable tracers of soil dust inputs (e.g. Hölzer and Hölzer, 1998;Shotyk et al, 2001). Lead and lead isotopes have been used to trace variation in atmospheric dust composition (e.g.…”
Section: Sourcingmentioning
confidence: 99%